THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CLIMATE ON EMPLOYEE JOB SATISFACTION AT CV BARIS JAYA INDONESIA - Barokatul Munawaroh; Syafi'ah; Latif, Elok Ainur (AmaNU: Jurnal Manajemen dan Ekonomi, 2025)
This research aims to determine the Influence of Leadership Style and Organizational Climate on Employee Performance at CV Baris Jaya Indonesia located in Kesugihan District, Cilacap Regency. This research uses a quantitative method by distributing questionnaires to 60 employees. Data analysis was carried out using multiple linear regression using SPSS. Based on the results of the research and data analysis, conclusions were obtained that showed that: (1) Leadership style partially has a significant effect on employee performance at CV Baris Jaya Indonesia. (2) Organizational climate partially has a significant effect on employee performance at CV Baris Jaya Indonesia. (3) Leadership style and organizational climate simultaneously have an effect on employee job satisfaction variables. Keywords: Leadership Style, Organizational Climate, and Job Satisfaction